The Effect of Tungsten Addition on Characteristics and Corrosion Performance of Plasma Electrolytic Oxidation Coating Created on Titanium - R. Yazdekhasti; K. Raeissi (Journal of Advanced Materials in Engineering)
This paper investigates the corrosion resistance properties of coatings produced by plasma electrolytic oxidation (PEO) on titanium in the presence of sodium tungstate (1 and 3 g/l). The coated samples were subjected to corrosion tests in sodium chloride solution to evaluate their protective performance. The samples containing tungsten had smaller porosity with a more uniform distribution. Also, the tungsten-containing coatings had an anatase phase, while the tungsten-free coating had both anatase and rutile phases. The results of the electrochemical impedance spectroscopy test showed the strong barrier performance of tungsten-containing coatings and their stability with the passage of immersion time. The coating with the highest percentage of tungsten and the thickness obtained from the bath with 3 g/l tungstate had the highest barrier resistance (886 kΩ.cm2) compared to other coatings. By increasing the immersion time, this coating could reach the highest value (997 kΩ.cm2) after 63 days of immersion by increasing the barrier resistance. This was while the lowest barrier resistance was related to the tungsten-free sample, which experienced a severe drop with increasing the immersion time.